Qhapaq Ñan: dilemas e ilusiones de una política del patrimonio - Sébastien Jallade (Bulletin de l'Institut Français d'Études Andines)
This article analyzes the Qhapaq Ñan project in Peru as a mechanism for encouraging a dialogue with Andean communities and for promoting their rights and development, even though it is presented as a successful intercultural experience by the state's culture sector. Through three examples (the «Semana Qhapaq Ñan», the emergence of the idea of community participation, and the emblematic case of the tinkuy of Aypate) it highlights the persistent conceptual and methodological shortcomings of this project. These not only lead to a form of instrumentalization of target audiences and their need. It leads us to emphasize that, as it is promoted today in its representations and practices, heritage is emblematic of the modern denial of indigenous difference rather than the opposite.